High thermal conductivity of the Earth's core and geodynamo - Reshetnyak M. Yu. (Vestnik MGTU, 2024)
The geomagnetic field is generated by dynamo processes in the Earth's core. This process is supported by the cooling of the planet and the growth of the solid core. It is known that the magnetic field existed long before the appearance of the solid core, although according to available estimates and calculations, this could not have happened. Moreover, according to some models, thermal conductivity in the Earth's core may be three times higher than generally accepted values. In this case, the magnitude of the convective heat flow decreases and the generation of the magnetic field stops. In the above-mentioned models it was assumed that the magnitude of the heat flow at the core – mantle boundary over the entire existence of the Earth linearly decreased by only 15–20 %. The latter is a rough guess. Significantly large changes in heat flow are predicted by models of mantle cooling, in which the growth of convective heat flow in ancient times occurs due to a decrease in the viscosity of the mantle with an increase in the temperature of the substance. Below we consider a model of the cooling of the Earth with a threefold value of the thermal conductivity of the core. It is shown that the use of a combined model of core and mantle cooling makes it possible to significantly increase the heat flow at the core – mantle boundary in ancient times. To slow down the growth of the solid core, a subadiabatic layer is included in the model. As a result, the size of the solid core in the model satisfies seismological observations. The model allows us to obtain a sufficient amount of energy to generate a geomagnetic field, starting from the moment the liquid core appeared and to the present. The appearance of a solid core 2.4 billion years ago, which does not lead to sharp changes in heat flow in the model, is consistent with paleomagnetic observations that do not record changes in the behavior of the magnetic field. The model does not exclude the existence of a multipole magnetic field at the initial stage.